Resveratrol Activates Autophagy via the AKT/mTOR Signaling Pathway to Improve Cognitive Dysfunction in Rats With Chronic Cerebral Hypoperfusion - Wang, Nan; He, Jinting; Pan, Chengliang; Wang, Jiaoqi; Ma, Ming; Shi, Xinxiu; Xu, Zhongxin (Frontiers in Neuroscience, 2019)
Chronic cerebral hypoperfusion (CCH) is a main cause of vascular dementia and is also an etiological factor of neurological diseases and mental disorders. However, few treatments are available for CCH, and new medications are needed. In the present study, we employed a rat model of CCH that was based on bilateral common carotid artery occlusion and investigated the therapeutic effects of resveratrol and its detailed mechanism of action. We evaluated neurological deficit scores and performed the Morris water maze test, hematoxylin and eosin staining, TUNEL staining, enzyme-linked immunosorbent assays, and Western blot. Resveratrol reduced neurological deficit scores in CCH rats and reduced pathological damage in the frontal cortex and hippocampus. Resveratrol activated autophagy and inhibited the expression of AKT/mechanistic target of rapamycin (mTOR) signaling pathway-related proteins. Treatment with a phosphoinositide-3 kinase inhibitor reversed the protective effect of resveratrol. These findings suggest that resveratrol improves cognitive function in a rat model of CCH and reduces oxidative stress-induced neuronal damage in the frontal cortex and hippocampus by activating autophagy and inhibiting neuronal apoptosis. These effects may be regulated by the AKT/mTOR signaling pathway.